Chercheurs et chercheuses en figure d’éditeur et d’éditrice dans la communication scientifique - Mounier, Pierre (Nordlyd, 2026)
This article explores the hybrid figure of the ‘researcher-publisher’, who plays an essential but often overlooked role in scientific communication. It offers a critical examination of traditional publishing models that strictly separate scientific and editorial roles, highlighting instead the profound interdependence between content and form. Through examples such as Johan Rooryck and the mutiny of the journal Lingua, it illustrates how the reappropriation of editorial functions by researchers allows them to regain scientific sovereignty in the face of commercial logic. The article also analyses the emergence of scholar-led publishers, seeing in this commitment a promise of autonomy and renewal for research.
Keywords: publishing; researcher; editing; Scholarly publishing